HUBUNGAN TINGKAT PENGETAHUAN TENTANG MENOPAUSE DENGAN TINGKAT KECEMASAN DALAM MENGHADAPI MENOPAUSE PADA WANITA USIA 40-50 TAHUN DI PEDUKUHAN PUGERAN MAGUWOHARJO SLEMAN - Antok Nurwidi Antara; Triana Uminingsih; Apliana Bulu (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2018)
ABSTRACTBackground: The menopause is very complex for women because they will experience changes in physical health that will affect their psychological health. Sufﬁ cient  knowledge about menopause can help premenop ausal women prepare themselves for menopause. The results of interviewswith 5 respondents found that women in Pugeran Hamlet did not know about menopause, did not understand the signs and symptoms, causes of menopause, and 2 out of 5 people said that they felt tense when feeling anxious, but vital signs, and felt uncomfortable.Objective: To determine the relationship of knowledge level about menopause with anxiety level in facing menopause in women ages 40-50 years in Pugeran Hamlet, Maguwoharjo, Sleman Method: This type of research is quantitative descriptive analytic using a correlation design and cross sectional approach. This research was conducted in November 2017 to October 2018. The population in this study were 86 people and the sample in this study amounted to 46 people. The sampling technique in this study used cluster random sampling technique. Results: The statistical test results from the relationship of knowledge level about menopause with anxiety level in facing menopause in women ages 40-50 years in Pugeran Hamlet, Maguwoharjo, Sleman, using the Spearman rank test with a signiﬁ cance level of α = 0.05 with p-value 0,000, this shows p-value <α (0,000 <0,05) which means there is a relationship between the level of knowledge about menopause with the level of anxiety in the face of menopause in women aged 40-50 years in Pugeran Hamlet, Maguwoharjo, Sleman. Conclusion: There is a relationship between the knowledge level about menopause with anxiety level in facing menopause in women ages 40-50 years in Pugeran Hamlet, Maguwoharjo, Sleman.